RELATIONSHIPS BETWEEN LEARNING INTERESTS, COURSE INTERACTIONS, AND PARENT’S ATTENTION WITH LEARNING RESULTS MATHEMATICS OF GRADE VIII - Adi Setya Priambudi; Aris Thobirin (Universitas Ahmad Dahlan, 2019)
Low student learning outcomes are related to various factors. Allegedly include interest in learning, peer interaction, and parents’ attention are several factors related to learning outcomes. This study aims to determine the presence or absence of a positive and significant relationship between interest in learning, peer interaction, and parents’ attention with mathematics learning outcomes of eighth-grade students of Islamic Junior High School (MTs) Miftahul Ulum Bulakan even semester academic year 2018/2019. MTs Miftahul’ Ulum Bulakan 2018/2019 school year consists of 3 classes. The population in this study is class VIII A, VIII B, and VIII C. The sampling technique uses class random sampling techniques and class VIII B as a sample class. Data collection techniques using the questionnaire method and the question method. Data collection instruments using questionnaires and math items. Analysis prerequisite tests include normality tests, independence tests, and linearity tests. Data analysis for hypothesis testing uses product-moment correlation analysis and multiple linear regression analysis. The results showed t positive and significant relationship between interest in learning, peer interaction, and parents’ attention to learning outcomes in mathematics. At a significant level of 5%, v1 = 3, v2 = 26, Fcount = 15.10592 and Ftable = 2.97515, so Fcount> Ftable with a multiple correlation coefficient of 0.79714 and a multiple regression equation for three variables namely . The relative contribution of = 62,75 %, = 0,36 %, = 36,89 % and the effective contribution = 39,87 %, = 0,23%, = 23,44%.